Study of the Effect of Nitric Acid in Electrochemically Synthesized Silicon Nanocrystals: Tunability of Bright and Uniform Photoluminescence - Alfredo Morales-Sánchez; María Antonia Cardona-Castro; Liliana Licea-Jiménez; Liliana Palacios-Huerta; Antonio Coyopol; Sergio Alfonso Pérez-García; Jaime Alvarez-Quintana; Mario Moreno (Nanomaterials, 2022)
In this work, we show a correlation between the composition and the microstructural and optical properties of bright and uniform luminescent porous silicon (PSi) films. PSi films were synthesized by electrochemical etching using nitric acid in an electrolyte solution. PSi samples synthesized with nitric acid emit stronger (up to six-fold greater) photoluminescence (PL) as compared to those obtained without it. The PL peak is shifted from 630 to 570 nm by changing the concentration ratio of the HF:HNO3:(EtOH-H2O) electrolyte solution, but also shifts with the excitation energy, indicating quantum confinement effects in the silicon nanocrystals (Si-NCs). X-ray photoelectron spectroscopy analysis shows a uniform silicon content in the PSi samples that emit the strongest PL. High-resolution transmission electron microscopy reveals that the Si-NCs in these PSi samples are about ~2.9 ± 0.76 nm in size and are embedded in a dense and stoichiometric SiO2 matrix, as indicated by the Fourier transform infrared analysis. On the other hand, the PSi films that show PL of low intensity present an abrupt change in the silicon content depth and the formation of non-bridging oxygen hole center defects.